Perancangan Fasade, Ruang Wudhu Dan Gharim, Serta Penataan Lanskap Kawasan Masjid Syifaunnas Dengan Pendekatan Arsitektur Masjid Nabawi - Saspriatnadi, Morian; Hidayat, Wahyu; Kuswoyo, Indra; Suryani, Lisa; Al Huseini, Muhd. Arief (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The mosque is a place of worship for Muslims. Masjid means place of prostration, also called musholla or langgar. In addition to places of worship, the mosque is also the center of the life of the Muslim community. The Prophet's Mosque is the first permanent mosque founded by the Prophet which functions to accomodate Islamic worship activities and the application of Islamic teachings. The Prophet's Mosque then became a model for the construction of subsequent mosques around the world. The Syifaunnas Mosque has been around for a long time so it is necessary to renew the mosque's facade according to the wishes of the local community to support the facilities and infrastructure of religious activities that are moving quite quickly such as education and mass activities. The management cooperates in service activities to realize the design document for the Syifaunnas mosque area. This activity uses qualitative descriptive by collecting data through observation and interviews. The activity approach is a bottom-up approach, namely by tracing user interests and desires. The result of this activity is to obtain a design document for the Syifaunnas mosque area by applying the architectural facade concept of the Prophet's mosque. In the design of the division based on zoning, namely the transition zone, mosque zone, and support zone. This document is useful for the Syifaunnas mosque development committee as a guide in the implementation of mosque construction.